(untitled) (International Conference on Computing, Artificial Intelligence and Information Systems, 2026)
In today’s era of globalization and digital technologies, the process of automation is developing rapidly across all sectors. Libraries, which are closely linked to education, science, and information systems, are not excluded from this process. Modern automated libraries are fundamentally different from traditional libraries, allowing users to receive fast, convenient, and high-quality services. As a result of the development of information technology, it is observed that libraries are transforming from mere book-houses into modern information centers.